The Influence of Marketing Mix on Loyalty Through Customer Satisfaction at Indomie Food Stalls (Warmindo) in Malang City - Fitriyah; Martaleni (Optima Science, 2023)
The purpose of this study is to analyze the effect of the 7P Marketing Mix relationship (Product, Price, Promotion, Place, People, Process, Physical Evidence) on Loyalty and / or through Customer Satisfaction at Indomie Food Stalls in Malang City. This research is an explanatory research with a quantitative approach. The variables in this study include Marketing Mix 7P (X), Customer Satisfaction (Y), and Loyalty (Z). The population in this study are Warmindo consumers in Malang City who have made more than 1 purchase and are more than 17 years old, the number of which is not known with certainty. The sample used was 351 respondents with the data collection method using a questionnaire. The data analysis used is Partial Least Square-Structural Equation Model (PLS-SEM) using the help of the SmartPLS 4 analysis tool. The results of research with male-dominated respondents show that the 7P marketing mix affects customer satisfaction but the location variable has no effect on customer satisfaction. Price and location variables have no effect on customer loyalty. There is an influence between customer satisfaction and customer loyalty. Price, product, promotion, people, process and physical appearance variables have a positive effect on loyalty through customer satisfaction while location variables do not.